PEMBENTUKAN PORTOFOLIO SAHAM DENGAN MENGGUNAKAN METODE MODEL INDEKS TUNGGAL DAN SECARA ACAK PERIODE PENELITIAN JANUARI 2013-DESEMBER 2017 - Andini Nurwulandari (GoAcademica Research dan Publishing, 2018)
A portfolio is described as a collection of investments and holdings made by investors, both individuals and institutions. This analysis employs a quantitative and descriptive analytic approach. Secondary data from the IDX LQ45 category's official website, which was successfully netted each month during the observation period, namely January 2013-December 2017. Random sampling was used to gather samples. The study's findings indicate that three optimal candidate portfolios were defined using a single index model; the candidate portfolio stocks are WIKA, ASRI, and SMGR. Using data from the LQ45 stock calculation for the period January 2013 to December 2017, we randomly selected two optimal portfolio candidates: ASRI and SMGR. The composition or proportion of funds obtained by each share is optimal for portfolio formation; the largest is WIKA's shares at 0.559948006 points, and the smallest is UNTR's shares at 0.559948006 points.